A pathological scapula in a mosasaur from the upper Maastrichtian of Antarctica: Evidence of infectious arthritis and spondyloarthropathy - Talevi, Marianella (2019)
Fil: Talevi, Marianella. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.